Impact of Emergency Medicine Technicians on Patient Survival and Outcomes: A Systematic Review - Alsadran Alyami, Alhassan Hussain; Al-Qahas, Ahmed Abdullah; Hussain AL MASNI, HUSSAIN Ali (Cuestiones de Fisioterapia, 2024)
Background: Emergency Medicine Technicians (EMTs) play a critical role in delivering prehospital emergency care. Their ability to provide timely and effective interventions significantly influences patient outcomes. Despite their essential role, the extent of their impact on patient survival and overall health outcomes remains underexplored in the literature.